2021
DOI: 10.3389/fcell.2021.625711
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of 20 Alphaviruses; Inter-species Diversity and Conserved Interactions Between Viral Non-structural Protein 3 and Stress Granule Proteins

Abstract: Alphaviruses infect a diverse range of host organisms including mosquitoes, mammals, and birds. The enigmatic alphavirus non-structural protein 3 (nsP3) has an intrinsically disordered, C-terminal hypervariable domain (HVD) that can interact with a variety of host proteins associated with stress granules (SGs). The HVD displays the highest variability across the more than 30 known alphaviruses, yet it also contains several motifs that are conserved amongst different subgroups of alphaviruses. For some alphavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…Early on it was found that SINV nsP3 is in complexes containing G3BP1 and G3BP2 [ 221 ]. The nsP3 proteins of other viruses were also found to colocalize with G3BP [ 222 ]. Of note is that several of the over 30 alphaviruses, which include a large number of mosquito-borne vertebrate pathogens [ 223 , 224 ], possess two FGxF-like motifs in nsP3.…”
Section: The Viral Response To Marylation Representing One Arm Of Inn...mentioning
confidence: 99%
“…Early on it was found that SINV nsP3 is in complexes containing G3BP1 and G3BP2 [ 221 ]. The nsP3 proteins of other viruses were also found to colocalize with G3BP [ 222 ]. Of note is that several of the over 30 alphaviruses, which include a large number of mosquito-borne vertebrate pathogens [ 223 , 224 ], possess two FGxF-like motifs in nsP3.…”
Section: The Viral Response To Marylation Representing One Arm Of Inn...mentioning
confidence: 99%
“…The ability of nsP3 to interact with various cellular proteins and functioning as gathering hubs also has allowed the formation of large cytoplasmic complexes [9,10,14,87,[129][130][131], which were suggested to regulate the host stress response during viral infection [108,129]. The OW alphaviruses SFV, SINV, CHIKV, and RRV and the NW alphavirus EEEV interact with mammalian G3BP family members and its mosquito homolog, Rasputin (Rin), forming the HVD-G3BP and HVD-Rin granule complexes in the cytoplasm of mammalian and mosquito hosts, respectively [32,132,133].…”
Section: Regulation Of Host Stress Responsesmentioning
confidence: 99%
“…The FMRP was suggested to suppress viral RNA translation by redirecting it into the host's stress granules. The interaction site is known as the Agenet-like domain binding motif [9,87,131,134]. Subsequently, the alphavirus nsP3 HVD is suggested to modulate the host stress response by interacting with stress granules' components and preventing host stress granule formation [32,[131][132][133].…”
Section: Regulation Of Host Stress Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mosquitoes are important biological vectors of many infectious viruses, including Getah virus (GETV), Ross River virus (RRV), chikungunya virus (CHIKV), Zika virus (ZIKV), and dengue virus (DENV), which were a menace to global public health and security (Sinclair and Asgari, 2020;Nowee et al, 2021;Pyke et al, 2021). Mosquitoes were considered as an intermediate host of numerous viruses that infect humans, animals, insects, plants, and other species (de Boer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%